Winding topologies of flux-switching motors for in-wheel traction. Issue 1 (5th January 2015) - Ahmed Masmoudi, Dr; Tang, Y.; Paulides, J.J.H.; Lomonova, E.A.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate winding topologies for flux-switching motors (FSMs) with various segment-tooth combinations and different excitation methods. Design/methodology/approach – For the ac winding of FSM, two winding topologies, namely the concentrated winding and the distributed winding, are compared in terms of the winding factor and efficiency. For the field winding of dc-excited FSM (DCEFSM), another two winding topologies, namely the lap winding and the toroidal winding, are compared in terms of effective coil area, end-winding length, and thermal conditions. Analytical derivation is used for the general winding factor calculation. The calculation results are validated using finite element analysis. Findings – Winding factors can be used as an indication of winding efficiency for FSMs in the same manner as done for synchronous motors. For FSMs with concentrated windings, the winding factor increases when the rotor tooth number approaches a multiple of the stator segment number. For FSMs with certain segment-tooth combinations, e.g. 6/8, the theoretical maximum winding factor can be achieved by implementing distributed windings. Furthermore, the toroidal winding can be an efficient winding topology for DCEFSMs with large stator diameter and small stack length. Research limitations/implications – This work can be continued with investigating the variation of reluctance torque with respect to different segment-tooth combinations of FSM. Originality/value – This paper proposes a general method to calculate the winding factor of FSMs using only the phase number, the stator segment number, the rotor tooth number, and the skew angle. Using this method, a table of winding factors of FSMs with different segment-tooth combinations is provided. Principle of design of FSMs with high-winding factors are hence concluded. This paper also proposed the implementation of distributed windings for FSM with certain segment-tooth combinations, e.g. 6/8, by which means a theoretical maximum winding factor is achieved. In addition, different winding topologies for the field winding of DCEFSM are also investigated.